One crazy summer - Williams-Garcia, Rita (Amistad, 2010)
In the summer of 1968, after travelling from Brooklyn to Oakland, California, to spend a month with the mother they barely know, eleven-year-old Delphine and her two younger sisters arrive to a cold welcome as they discover that their mother, a dedicated poet and printer, is resentful of the intrusion of their visit and wants them to attend a nearby Black Panther summer camp.